Assessing the progression of segmental fibrosis in chronic liver disease using extracellular volume fractions. Issue 145 (December 2021) - Ozaki, Kumi; Ishida, Tomokazu; Ohtani, Takashi; Shimada, Masato; Kimura, Hirohiko; Gabata, Toshifumi
Abstract: Purpose: To assess the segmental difference of liver fibrosis during the progression of chronic liver disease (CLD) using hepatic extracellular volume fractions (fECVs) obtained by dual-energy CT. Methods: A total of 218 patients (92 men and 126 women; mean age, 67.8 ± 11.7 years) with CLD and 85 patients (44 men and 41 women; mean age, 62.8 ± 13.7 years) without CLD as a control underwent dual-energy computed tomography (CT) of the liver (5-min equilibrium phase images). The iodine densities of the lateral, medial, anterior, and posterior segments and the aorta were measured, and fECVs were calculated. Comparisons of the fECV of each segment and for each albumin–bilirubin (ALBI) grade were then statistically analyzed. Results: In the control group and ALBI grades 1 and 3, no significant difference in fECV was found between each segment, whereas in ALBI grade 2, the fECVs were significantly larger in the medial and anterior than in the other segments ( p < 0.001). The fECVs of the lateral and posterior segments significantly increased with higher ALBI grade ( p < 0.001). The fECVs of the medial and anterior segments were significantly increased with higher ALBI grade, up to grade 2 ( p < 0.001), but no significant difference was found between ALBI grades 2 and 3. Conclusion: During the progression of CLD, fibrosis antecedently progressed in the medial and anterior segments, followed by the other liver segments.